Study on physicochemical parameters and distribution of phytoplankton in Kuantan estuary, Pahang - Khan Chowdhury, Ahmed Jalal; John, Akbar; Sheikh, Hassan Ibrahim; Saad, Shahbudin (Razi Publishing, 2017)
A study on physicochemical parameters and distribution of phytoplankton communities was carried out at Kuantan estuary, Pahang, Malaysia. The study was carried out in September, 2011 and November, 2011 to determine the spatial distribution of phytoplankton from three different stations during the pre-monsoon and monsoon seasons. The phytoplankton and water quality were analyzed using standard method outlines by APHA, 1998. The temperature recorded was between 27.29 oC to 29.33 oC, pH was from 6.96 to 8.24, conductivity range from 33.50mS/cm to 47.85mS/cm, dissolved oxygen ranged was from 4.25 mg/L to 5.84 mg/L, biochemical oxygen demand was from 3.37 mg/L to 1.60 mg/L, salinity range from 21.01 ppt to 30.72 ppt, total dissolved solids range from 21.80 g/L to 31.60 g/L and total suspended solids range from 0.024 to 0.044. The nitrite concentration was range from 0.078 mg/L to 0.088 mg/L during monsoon while in the pre-monsoon seasons the range was from 0.018 mg/L to 0.025 mg/L. Similarly, ammonium concentration was from 0.3056 mg/L to 0.0670 mg/L. The phosphorus content was range from 0.0110 mg/L to 0.0897 mg/L. The pre-monsoon season phytoplankton (1466 Cells/L) was found to be higher than the monsoon season phytoplankton (644 Cells/L)